2017
DOI: 10.1111/jphp.12721
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of natural and synthetic alkamides involves TRPV1 receptors

Abstract: These results suggest that alkamide affinin, longipinamide A, longipenamide A and longipenamide B isolated from Heliopsis longipes as well as the synthesized analogue compounds N-isobutyl-feruloylamide and N-isobutyl-dihydroferuloylamide produce their effects by activating TRPV1 receptor and they may have potential for the development of new analgesic drugs for the treatment of orofacial pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…COX catalyzes the conversion of arachidonic acid to prostaglandin ( Williams et al, 1999 ), leading to the activation and sensitization of peripheral nociceptors. Since the vast majority of studies of alkamides shows their peripheral antinociception effects ( de la Rosa-Lugo et al, 2017 ), on the basis of the Rimbau et al (1999) study and our current findings, we suggest that the peripheral anti-nociception activity of AEAPR and MEAPR may be due to their alkamides.…”
Section: Discussionsupporting
confidence: 61%
“…COX catalyzes the conversion of arachidonic acid to prostaglandin ( Williams et al, 1999 ), leading to the activation and sensitization of peripheral nociceptors. Since the vast majority of studies of alkamides shows their peripheral antinociception effects ( de la Rosa-Lugo et al, 2017 ), on the basis of the Rimbau et al (1999) study and our current findings, we suggest that the peripheral anti-nociception activity of AEAPR and MEAPR may be due to their alkamides.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, the partial inhibition of the α-sanshool-induced convulsions by the TRPV1-antagonist capsazepine suggests that this alkamide induces the seizures, at least in part, by stimulating the TRPV1 channels (▶Table 2). It is possible that convulsions induced by affinin, capsaicin, and the synthetic alkamide reported by de la Rosa et al [7] also occur via the same mechanism. Additional experimental data are required to assess this statement.…”
Section: Discussionmentioning
confidence: 87%
“…and the synthetic alkamide N-isobutyl-dihydroferuloylamide (180 mg/kg, i.p.) in mice [7]. In that work, the authors found that affinin did not induce seizures at doses lower than 90 mg/kg (i.p.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For pharmacological assays, the alkamide samples were prepared with saline solution, DMSO (10%), Tween 80 (5%), and ethanol (1%). capsaicin (420 mg) obtained according to previous reports (de la Rosa-Lugo et al, 2017;Déciga-Campos et al, 2010;Rios et al, 2007). In summary, affinin was isolated from an H. longipes acetone extract and capsaicin was obtained from a Capsicum chinese dichloromethane extract.…”
Section: Chemical Agents (Abbreviation Pubchem Cid)mentioning
confidence: 98%